The federal question and measures to tackle the Covid-19 pandemic (Revista do Tribunal Regional Federal da 3ª Região, 2021)
The increase in the role of judiciary in drawing up and implementing public policies is not an isolated Brazilian phenomenon. Nor is it limited to public health policy, as it has encompassed institutional policy itself. Every day we witness the judicialization of politics. Sessions of the Supreme Court have become more relevant than sessions of the National Congress. We know the name and have an opinion on each of the ministers. In other times, it was rare for anyone to know the name of the then president of the Supreme Court. The expansion of the role of the judiciary gained momentum with the development of neo-constitutionalism after the Second World War. The Constitution ceased to be a charter of principles that disciplined political power and began to have normative force. The development of control of constitutionality centralized in a constitutional court made the normative force of the Constitution present in citizens' daily lives. From then on, what is written in the Constitution is valid and must be complied with. The day after a law is published, its constitutionality is challenged before the Supreme Court. This is the third stage of politics, the outcome of which depends on the interpretation of the compatibility of the rule approved in the political forum with the Constitution itself. The Covid-19 pandemic has emerged amid this scenario of intense judicialization of politics. It was predictable that the conflicting views on how to deal with it would end up in the Judiciary, either with the district judge or the Supreme Court. We could look at judicialization of public policies to tackle Covid-19 from various perspectives. We have opted for a focus on the federative conflict arising from the adoption of measures to combat the health calamity in the various spheres of power. This is our theme.
Keywords: Cooperative federalism; public policies; constitutional competence in health matters; covid-19; public health; ADI 6.341 STF